Peran Literasi Keuangan, Risk Tolerance, dan Risk Perception Terhadap Keputusan Investasi Mahasiswa - Alivazain Brillianti Zahida (UMSurabaya Publishing, 2021)
Economic development requires individuals to manage their finances both long term and short term. This research aims to test and prove that there is an effect of financial literacy, risk tolerance, and risk perception on investment decisions of students in Faculty of Economics and Business, Muhammadiyah University of Surabaya. This research uses a quantitative approach, the population of this research is the students in Faculty of Economics and Business, Muhammadiyah University of Surabaya with a sample of 93 students using purposive sampling technique. Data were collected by means of a questionnaire distributed through a G-form which had previously been tested for validity and reliability. The test method uses Multiple Linear Analysis with SPSS for Windows Version 21 Program. The results show that: (a) Financial Literacy has a significant positive effect on Investment Decisions: (b) Risk Tolerance has a significant positive effect on Investment Decisions: (c) Risk Perception has a positive but not significant effect on Investment Decisions: (d) Financial Literacy, Risk Tolerance, and Risk Perception have a significant positive effect simultaneously on the investment decisions of students in Faculty of Economics and Business, University of Muhammadiyah Surabaya. Perkembangan perekonomian menuntut individu dalam mengelola keuangan mereka baik jangka panjang maupun jangka pendek. Penelitian ini bertujuan untuk menguji dan membuktikan bahwa terdapat pengaruh literasi keuangan, risk tolerance, dan risk perception terhadap keputusan investasi mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surabaya. Penelitian ini menggunakan pendekatan kuantitatif, populasi dari penelitian ini adalah mahasiwa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surabaya dengan sampel sebanyak 93 mahasiswa menggunakan teknik purposive sampling. Data dikumpulkan dengan kuesioner yang di sebar melalui gform yang sebelumnya telah diuji validitas dan reabilitasnya. Metode pengujian menggunakan Analisis Linier Berganda dengan Program SPSS for Windows Versi 21. Hasil penelitian menunjukkan bahwa: (1) Literasi Keuangan berpengaruh positif signifikan terhadap Keputusan Investasi: (2) Risk Tolerance berpengaruh positif signifikan terhadap Keputusan Investasi: (3) Risk Perception berpengaruh positif tetapi tidak signifikan terhadap Keputusan Investasi: (4) Literasi Keuangan, Risk Tolerance, dan Risk Perception berpengaruh positif signifikan secara simultan terhadap Keputusan Investasi mahasiswa FEB Universitas Muhammadiyah Surabaya.Kata Kunci: Literasi keuangan, risk, totelarance, risk perception, keputusan investasi